Primigravida with Fetal Malpresentation and Bicornuate Uterus: A Case Report - Christofel Panggabean; Mirza, Muhammad Syauqi; Michelle Putri (Phlox Institute: Indonesian Medical Research Organization, 2024)
Introduction: Malpresentation of the fetal head in left oblique presentation is a rare obstetric complication but has the potential to cause birth difficulties. This condition can be worsened by anatomical abnormalities of the uterus such as a bicornuate uterus. Case presentation: An 18-year-old primigravida presented with complaints of labor and premature rupture of membranes. Examination revealed malpresentation of the fetal head in left oblique presentation, and further ultrasound examination revealed a possible bicornuate uterus. Conclusion: Careful labor management and appropriate surgical intervention, in this case, an emergency caesarean section, resulted in the birth of a healthy baby girl. This case emphasizes the importance of early diagnosis and a multidisciplinary approach in treating complex cases of fetal malpresentation.